Electric powered self-tilting trike : design and development of a tilt by wire system Part 2 - Jefferson (2015)
The aim of this research is to maximize the efficiency of a vehicle especially in a sharp turn by using tilting mechanism. Unlike bicycle which can tilt while turning in a high speed, 3 or 4 wheels vehicle loses some energy in turning due to the lack of stability caused by centrifugal force. The proposed approach is by combining the efficiency provided by tilting mechanism and the convenience and safety from a conventional car. The inability of a conventional car to tilt as a bike in a curve is proven to cost it to lose its stability and hence its efficiency. When a vehicle turns in a high speed, one of its outer wheel will eventually lost its traction and the energy will be wasted. On the other hand, tilting mechanism provides some leeway for the tilting resultant force to consistently fall in between the wheel base region, so that the vehicle can turn faster stably. However, to ride a vehicle which enable tilting is not intuitive for everyone since it requires the ability to ride a bike and a low centre of gravity point makes it extremely hard to tilt using body weight. Hence, the idea of creating an automatic tilt vehicle or tilt by wire comes alive. [2nd Award]